HUBUNGAN ANTARA MODEL LEARNING CYCLE 7E DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SEKOLAH DASAR: SEBUAH STUDI LITERATUR - Ayu, Dwi Hadita; Judijanto, Loso; Hendrilia, Yudi; Ramadhona, Rossa; Prananda, Gingga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to analyze the relationship between the application of the 7E Learning Cycle model and improving elementary school students' critical thinking skills through literature study. Using the literature study method, this research examines publications from relevant national and international journals, focusing on the keywords